Nivel de apoyo emocional brindado por la enfermera a pacientes en fase preoperatoria Hospital Víctor Lazarte Echegaray - Escobedo Solis, María Isabel (2014)
The present work quantitative, descriptive, prospective, cross-sectional type, was carried out in the A and B Surgical Services of the Victor Lazarte Echegaray Hospital in 2010, with the objective to determine the level of emotional support provided by the nurse to the needs of inclusion, control and affection of surgical patients in preoperative phase. The sample consisted of 286 patients who were applied a survey format it was validated for its application, then the analysis came to the following conclusions : The level of emotional support given by the nurse to the need for inclusion is mostly fair to good (52.7 % , 37.6 % respectively ) and only 9.7 % on a bad level , the level of emotional support given by the nurse to the need for control is more qualified rate as fair to good (46.2 % and 41.9 % respectively) and 11.8 % is bad , the level of emotional support given by the nurse to the need for affection is mostly good to fair (47.3 % and 42.5 % respectively) and 10.2 % bad, the level of emotional support given by the nurse to the needs of inclusion , control and affection, is largely a fair to good level (57 %, 43 % respectively).